2017
DOI: 10.3906/vet-1610-22
|View full text |Cite
|
Sign up to set email alerts
|

Addition of molasses, corn steep liquor, and rice polish as economical sources to enhance the fungal biomass production of wheat straw by Arachniotus sp.

Abstract: This study was planned to see the additive effects of various industrial residues including molasses, rice polish, and corn steep liquor for the bioprocessing of wheat straw (WS) through solid-state fermentation (SSF) using Arachniotus sp. as a fermenting agent. The performance of fungal-based WS (seed culture) was evaluated in terms of the favorable changes in crude protein (CP) contents. WS (5 g) was mixed with our selected carbon and nitrogen sources in a basal medium containing optimized salt concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Fermentation. In general, Shahzad et al (2017) reported that CSL is composed of carbohydrates, peptides, essential amino acids, minerals, vitamins and unidentified organic and inorganic compounds to rice straws ensilage. Hence, lactic acid bacteria in silage are able to ensure fast and vigorous fermentation because of their rapid accumulation of lactic acid and lower pH values at earlier stages of ensiling (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fermentation. In general, Shahzad et al (2017) reported that CSL is composed of carbohydrates, peptides, essential amino acids, minerals, vitamins and unidentified organic and inorganic compounds to rice straws ensilage. Hence, lactic acid bacteria in silage are able to ensure fast and vigorous fermentation because of their rapid accumulation of lactic acid and lower pH values at earlier stages of ensiling (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…CSL is a source of elemental nutrients such as nitrogen, reducing sugars, minerals, proteins, enzymes, organic acids and vitamins. In the chemical industry, CSL as a low cost substrate is widely used in fermentation processes [35][36][37].…”
mentioning
confidence: 99%